Ojeada a la Transmisión de los Signos Mágicos Antiguos: Tres Objetos Rituales con Texto Procedentes de Pérgamo - Dzwizen, Kirsten (International Journal of Ancient Astrology and Magic Research, 2015)
The paper is focused on a new discovery of a rare repetitive sequence of ancient magical signs inscribed on three stone artefacts from Pergamon. The results of a new analysis lead to a re-interpretation of the artefacts and contribute in two ways to the research in late antique ritual practice: They enrich our fragmentary knowledge of the writing practice of magical signs and provide new information about the transmission of texts inscribed on artefacts. The paper is structured as follows: I will first provide a short overview of the occurrence and application of magical signs in antiquity. This will be followed by a summary of the earlier description and interpretation of the three textual stone artefacts. Based especially on the analysis of the sequences of magical signs these interpretations will then be refuted step by step and re-evaluated, leading to a new reconstruction of the entire inscribing process. Subsequently alternative interpretations of the stone artefacts will be outlined in brief. The final conclusion includes a discussion of present interpretations of ancient magical signs.